A qualitative study describing nursing home nurses sensemaking to detect medication order discrepancies - Amy Vogelsmeier; Ruth A. Anderson; Allison Anbari; Lawrence Ganong; Amany Farag; MaryAnn Niemeyer (BMC, 2017)
Abstract Background Medication reconciliation is a safety practice to identify medication order discrepancies when patients' transitions between settings. In nursing homes, registered nurses (RNs) and licensed practical nurses (LPNs), each group with different education preparation and scope of practice responsibilities, perform medication reconciliation. However, little is known about how they differ in practice when making sense of medication orders to detect discrepancies. Therefore, the purpose of this study was to describe differences in RN and LPN sensemaking when detecting discrepancies. Method We used a qualitative methodology in a study of 13 RNs and 13 LPNs working in 12 Midwestern United States nursing homes. We used both conventional content analysis and directed content analysis methods to analyze semi-structured interviews. Four resident transfer vignettes embedded with medication order discrepancies guided the interviews. Participants were asked to describe their roles with medication reconciliation and their rationale for identifying medication order discrepancies within the vignettes as well as to share their experiences of performing medication reconciliation. The analysis approach was guided by Weick's Sensemaking theory. Results RNs provided explicit stories of identifying medication order discrepancies as well as examples of clinical reasoning to assure medication order appropriateness whereas LPNs described comparing medication lists. RNs and LPNs both acknowledged competing demands, but when performing medication reconciliation, RNs were more concerned about accuracy and safety, whereas LPNs were more concerned about time. Conclusions Nursing home nurses, particularly RNs, are in an important position to identify discrepancies that could cause resident harm. Both RNs and LPNs are valuable assets to nursing home care and keeping residents safe, yet RNs offer a unique contribution to complex processes such as medication reconciliation. Nursing home leaders must acknowledge the differences in RN and LPN contributions and make certain nurses in the most qualified role are assigned to ensure residents remain safe.